Project-based Learning Approach in a Research Methods Class: Students Experiences - Muhammad Mukhtar Aliyu (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
Undergraduate final year projects are problematic in many Nigerian universities especially in terms of knowledge of research and writing skills among others. Teaching and learning methods have always been key factors responsible for the problems. Therefore, the current study adopts a project-based learning approach in teaching and learning the research method course for third-year undergraduates in a university in Nigeria. It hopes to provide a greater insight to develop an effective teaching and assessment strategy for the course. This paper specifically presents the students experiences in learning the course using the PBL approach. Data were collected using semi-structured interviews and reflective writing journals. The data were analysed using qualitative data analysis steps identified by Braun and Clarke (2006). The findings of the study show that the participants have positive perceptions of the approach because it enables them to learn the basics of research and improve their language skills. However, they found the approach to be demanding, and time-consuming. The study identifies some implications for practice and makes some suggestions for further studies.